Argosfestival 2005. - Buxmann, Anke; Depraetere, Frie; Argos, Brussel (Brussel : Argos Editions, 2005)
Akerman, Chantal ; Anastas, Ayreen ; Augustijnen, Sven ; Baes, Pascal ; Bardin, Olivier ; Beaubois, Franck ; De Bemels, Antonin ; Benning, James ; Bergman, Marta ; Van Berkelaer, Gert ; Bernadette Corporation ; Bernier, Pascal ; Bianconi, Loredana ; Blondeel, Maria ; De Boe, Rik ; Brakhage, Stan ; Bucher, Francois ; Buchet, Jean-Marie ; Buckingham, Matthew ; Bucquoy, Jan ; Case, Charley ; Cash, Robert ; Catrysse, Wim ; Cattelain, Claude ; De Clercq, Anouk ; Convert, Jean-Philippe ; Coppin, Christian ; Cornelis, Jef ; Crabeels, Cel ; De Cupere, Peter ; D'Haeseleer, Kurt ; d'Ursel, Laurent ; Dekegel, Olivier ; Dekyndt, Edith ; Delauney, Nathalie ; Deller, Jeremy ; Denicolai, Simona ; Desamory, Lucile ; Dierckx, Isabelle ; Downsbrough, Peter ; Duyckaerts, Eric ; Eckhardt, Julia ; Engels, Ludo ; Fichefet, Frédéric ; Figgis, Mike ; Fontaine, Thierry ; François, Michel ; Gauthier, Hubert ; Gigounon, Bernard ; Grimonprez, Johan ; Hayes, Sharon ; Hynninen, Mikko ; Jacquemin, Frédéric ; De Kegel, Jan ; Van Kerckhoven, Anne-Mie ; Van Lancker, Laurent ; Lehman, Boris ; Lennep, Jacques ; Lheureux, Christelle ; Liping Weng & Meys, Olivier ; Lorand, Michel ; Maréchal, Nicolas ; Martin, Marie-France & Patricia ; Martin, Simon ; Mas, Aurore Del ; Meessen, Vincent ; Menick, John ; Messieurs Delmotte ; De Mey, Thierry ; Mouton, Joseph ; Novak, Stepan ; Ohanian, Melik ; Op de Beeck, Hans ; Pacquée, Ria ; Van Paesschen, Bram ; Pasolini, Pier Paolo ; Penders, Anne ; Philipsz, Susan ; Provoost, Ivo ; Ra'ad, Walid ; Rafael ; Restrepo, José Alejandro ; van Riel, Els ; Robin, Gwendoline ; Robinson, Mark ; Rowe, Keith ; Sanborn, Keith ; Smith, John ; Stallaert, Luk ; Suzuki, Ai ; Theys, Koen ; Tuerlinckx, Joëlle ; Vanagt, Sarah ; Vandeweerd, Pierre-Yves ; Vanrunxt, Marc ; etc.
Argosfestival 2005, Brussel, 13 - 22.10
boek